Is Dutch Auction Suitable for Decomposable Tasks in Competitive Crowdsourcing Markets? - Mridha, Sankar Kumar; Bhattacharyya, Malay (Human Computation, 2017)
Competitive crowdsourcing is a popular strategic model for solving tasks in an efficient economical way. Competitive crowdsourcing platforms generally choose the winners for a single indivisible task following the conventional Dutch auction to minimize the cost. In this paper, we show that when the tasks are decomposable such mechanisms become biased for competitive crowdsourcing markets. As a solution to this, we suggest a variant of the Dutch auction (referred to as time-invariant Dutch auction) for solving decomposable tasks. Overall, some new insights about the mechanism design for competitive crowdsourcing markets are obtained.